Analysis of Public Satisfaction with The Comfort of the Waiting Area at Tegal City Station - Cahyanti, Antika Tri; Vijayo, Charrly Dittha; Putranti, Chika Aulia; Brilianti, Dani Fitria (Kirana Publisher (KNPub), 2024)
High-quality public services are essential for addressing citizens' needs and enhancing their experiences with government-provided amenities. The primary aim of this research is to evaluate the level of satisfaction among passengers utilizing the waiting room facilities at Tegal City Rail Station, with a focus on comfort, cleanliness, accessibility, and overall service quality. A questionnaire survey method was employed to gather feedback from passengers, who were asked to rate various aspects of the waiting room services. The collected data were analyzed to identify key factors influencing satisfaction levels and to provide insights into potential areas for improvement. The findings reveal both strengths and specific elements that could be enhanced to better meet public expectations. This study contributes to ongoing efforts to improve public service quality in transportation facilities, promoting a more comfortable and efficient environment for passengers.